Data from: The comparative genomic landscape of adaptive radiation in Crater Lake cichlid fishes - Xiong, Peiwen; Hulsey, C. Darrin; Fruciano, Carmelo; Wong, Wai Y.; Nater, Alexander; Kautt, Andreas F.; Simakov, Oleg; Pippel, Martin; Kuraku, Shigehiro; Meyer, Axel; Franchini, Paolo (Dryad, 2020)
Factors ranging from ecological opportunity to genome composition might
explain why only some lineages form adaptive radiations. While being rare,
particular systems can provide natural experiments within an identical
ecological setting where the factors promoting increased species numbers
and phenotypic divergence in two closely related lineages is notably
different. We investigated one such natural experiment using two de novo
assembled and 40 re-sequenced genomes and asked why two closely related
Neotropical cichlid fish lineages, the Amphilophus citrinellus species
complex (Midas cichlids; radiating) and Archocentrus centrarchus (Flyer
cichlid; non-radiating), have resulted in such disparate evolutionary
outcomes. Although both lineages inhabit many of the same Nicaraguan
lakes, whole-genome inferred demography suggests that priority effects are
not likely to be the only cause of the dissimilarities. Also, genome-wide
levels of selection, transposable element dynamics, gene family expansion,
major chromosomal rearrangements, and the number of genes under positive
selection were not markedly different between the two lineages. To more
finely investigate particular subsets of the genome that have undergone
adaptive divergence in Midas cichlids, we also examined if there was
evidence for molecular pre-adaptation in regions identified by QTL mapping
of repeatedly diverging adaptive traits. Although most of our analyses
failed to pinpoint substantial genomic differences, we did identify
functional categories containing many genes under positive selection that
provide candidates for future studies on the propensity of Midas cichlids
to radiate. Our results point to a disproportionate role of local, rather
than genome-wide factors underlying the propensity for these cichlid
fishes to adaptively radiate.
The method for the genomes and transcriptomes assemblies was described in
the paper "The Comparative Genomic Landscape of Adaptive Radiation in
Crater Lake Cichlid Fishes".
Keywords: FOS: Biological sciences